1963
DOI: 10.1113/jphysiol.1963.sp007137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium on the conductance change of the end‐plate membrane during the action of transmitter

Abstract: It is well known that the external concentration of calcium has a marked influence on the ordinary muscle membrane (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(73 citation statements)
references
References 36 publications
2
70
1
Order By: Relevance
“…Both of these kinases phosphorylate the ACh receptor (Huganir & Greengard, 1987;. Further, acetylcholine-gated endplate channels are permeable to calcium (Takeuchi, 1963). Therefore, calcium influx occurs at the endplate during exposure to nicotinic agonists, which in turn causes an elevation of the intracellular ionized calcium concentration near the inner surface of the postsynaptic membrane (Parsons & Nastuk, 1969;Manthey, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these kinases phosphorylate the ACh receptor (Huganir & Greengard, 1987;. Further, acetylcholine-gated endplate channels are permeable to calcium (Takeuchi, 1963). Therefore, calcium influx occurs at the endplate during exposure to nicotinic agonists, which in turn causes an elevation of the intracellular ionized calcium concentration near the inner surface of the postsynaptic membrane (Parsons & Nastuk, 1969;Manthey, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have shown that Ca2+ enters the endplate of vertebrate skeletal muscle as a consequence of agonist action on the endplate channels (Jenkinson & Nicholls, 1961;Takeuchi, 1963;Evans, 1974;Miledi et al, 1980). In our experiments with ECO the agonist is probably ACh released from the nerve terminals.…”
Section: Methodsmentioning
confidence: 59%
“…In unstimulated tissues, the amount released non-quantally from the nerve is about ten times greater than that released quantally (Miledi et al, 1983 & Vyskocil, 1979;Dolezal & Tucek, 1983;Stanley & Drachman, 1983) and is from the cytoplasm of the nerve (Molenaar et al, 1987 (Adams et al, 1986). In this regard, Jenkinson & Nicholls (1961) and Takeuchi (1963) reported abolition by Mg2+ of the local contracture normally found after ACh. Evans (1974) found that an increased [Mg2 ].…”
Section: Methodsmentioning
confidence: 84%
“…So, a local shortening of the MEP was attributed to a local increase of the Ca 2+ -concentration . Additionally, an influx of Ca 2+ by means of activated acetylcholine receptors (Takeuchi, 1963) or opened Na + -channels of subsynaptic folds (Beam et al, 1985) could be the cause of a local increase of the Ca 2+ -concentration.…”
Section: /4mentioning
confidence: 99%